Perbandingan Komposisi dan Pertanggungjawaban Organ Perseroan dalam Anggaran Dasar Perseroan Serta Minimal Pemegang Saham antara Hukum Perseroan Indonesia dan Beberapa Negara Non-Civil Law - Fabiola, Bella; Sendrawan, Tjhong (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
The actions of the organs of a Limited Liability Company (PT) are limited by the Articles of Association of the Company itself. But behind the Company's Articles of Association, of course there is the Company Law which limits the provisions regarding PT. The limitations in the UUPT are not necessarily universal. This fact causes the Company's Articles of Association to have provisions that are different from the constitutional documents of PTs in other countries. Based on this, the question that arises is what are the differences between the provisions of the Company Law and other countries, especially in terms of the organs contained in the Company. The research method used in writing this article is a normative juridical research method. The research specifications used in this research are analytical descriptive. The data analysis method used is normative qualitative.From the comparative study in this paper, a number of legal gaps can be identified in Indonesian law that need to be corrected. First, the Company Law has not yet concretely explained the limits of the Directors' responsibilities, leaving legal uncertainty regarding the limits of the Directors' responsibilities. Second, the role of the Board of Commissioners seems unnecessary because it can be transferred to existing Company organs. Therefore, the Board of Commissioners needs to be given a clearer role in the Articles of Association. Third, there is no concrete reason for the prohibition on single share ownership.